The Elephant in the Nursery: Paediatric Exceptionalism? - Anderson, James; Zlotnik Shaul, Randi; Bianchi, Andria (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2024)
Prior to the COVID-19 pandemic (hereafter, ‘the pandemic’), there was already widespread concern about the adequacy of health care resources across Canada. The COVID-19 pandemic exacerbated these concerns exponentially, widening already significant cracks in provincial health care systems. Currently the system is struggling with the exacerbation of wait times for surgeries previously delayed by mandated closures during the pandemic. In Ontario, the backlog of surgeries, and associated backlogs in radiology and other services critical to paediatric care, led to the creation of a consortium of paediatric hospitals committed to advocacy for more funding for paediatrics. Thus far, the provincial and federal governments have agreed to a one-time cash infusion, but the consortium is calling for a permanent increase in funding for paediatrics. A challenge is that the adult sector has also suffered from delays and backlogs. Furthermore, as already noted, older adults have borne the brunt of morbidity and mortality associated with COVID-19. The challenge for the paediatric sector is whether and how to defend the prioritization of children and youth. In this paper, we review four approaches to just allocation – utilitarian ageism, fair innings, the prudential lifespan approach, and prioritarian ageism – and examine their strengths and weaknesses. We conclude by endorsing prioritarian ageism (prioritarianism). Prioritarianism retains the strengths of utilitarian ageism and fair innings while avoiding their weaknesses. Furthermore, because prioritarianism does not treat age as an independent moral criterion, allocation schemes based on this foundation are less susceptible to legal challenge and may be more palatable to the general public.